2015
DOI: 10.1371/journal.pone.0126284
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Parenting Behaviors in California Mice, a Monogamous Rodent Species, by Endocrine Disrupting Chemicals

Abstract: The nature and extent of care received by an infant can affect social, emotional and cognitive development, features that endure into adulthood. Here we employed the monogamous, California mouse (Peromyscus californicus), a species, like the human, where both parents invest in offspring care, to determine whether early exposure to endocrine disrupting chemicals (EDC: bisphenol A, BPA; ethinyl estradiol, EE) of one or both parents altered their behaviors towards their pups. Females exposed to either compound sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 52 publications
1
57
0
Order By: Relevance
“…This has been shown to occur in various rodent models where the dams are exposed to BPA and/or related EDC (Boudalia et al, 2014; Cummings et al, 2005; Della Seta et al, 2005; Engell et al, 2006; Johnson et al, 2015; Kundakovic et al, 2013; Palanza et al, 2002). Potential poor parenting received by the BPA-exposed pups may place them at risk for learning and memory deficiencies and other behavioral deficits (Birnie et al, 2013; Dougherty et al, 2013; Parent et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This has been shown to occur in various rodent models where the dams are exposed to BPA and/or related EDC (Boudalia et al, 2014; Cummings et al, 2005; Della Seta et al, 2005; Engell et al, 2006; Johnson et al, 2015; Kundakovic et al, 2013; Palanza et al, 2002). Potential poor parenting received by the BPA-exposed pups may place them at risk for learning and memory deficiencies and other behavioral deficits (Birnie et al, 2013; Dougherty et al, 2013; Parent et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, mice and deer mice ( Peromyscus maniculatus bairdii ) developmentally exposed to environmentally relevant concentrations of BPA show increased anxiety-like behaviors [17; 71; 72; 73; 74; 75]. Several rodent studies have shown that BPA exposure can reduce maternal and even paternal care [15; 22; 72; 76]. The current studies indicate that BPA-alternatives can alter gene involved in the dopamine-serotonin systems in the prefrontal cortex, which might account for some of the observed behavioral disruptions [65].…”
Section: Neuroendocrine Disruption Due To Exposure Of Rodent Models Tmentioning
confidence: 99%
“…However, it is also becoming apparent that exposure to BPA, especially during development, can result in neurobehavioral and other disorders [2; 3; 4; 5; 6; 7; 8; 9; 10; 11; 12; 13; 14]. Examples of neurobehavioral disorders that have been associated with BPA in rodent and other animal models include cognitive deficits, increased anxiety, socio-sexual deficiencies, compromised maternal and/or paternal care, and decreased voluntary physical activity [15; 16; 17; 18; 19; 20; 21; 22; 23]. Evidence also links exposure to this chemical to neurological disorders, such as autism spectrum disorder (ASD) and attention deficit hyperactivity disorder (ADHD) [2; 3; 4; 5; 6; 7; 8; 9; 10; 11; 24; 25; 26; 27].…”
Section: Introductionmentioning
confidence: 99%
“…In the California mouse, a monogamous species with bi-parental care, prenatal and neonatal exposure of mice to BPA decreased subsequent maternal behavior in females. Although paternal behavior was not significantly affected by BPA exposure, females paired with BPA-exposed males showed reduced engagement in maternal care [34•]. Accordingly, male deer mice that were perinatally exposed to BPA were less attractive for females, which preferred unexposed control males to BPA-exposed males in a mate choice test [14].…”
Section: Behaviormentioning
confidence: 99%
“…Maternal exposure during pregnancy through a non-stressful administration procedure (i.e., allowing pregnant female mice to drink corn oil in which the compound is dissolved) to a low, environmentally relevant dose of BPA produced subtle alterations in subsequent maternal behavior and in their offspring’s behavioral development [5]. Further studies in rats [33,54], mice [12••], voles [55] and Peromyscus (P. California; [34•]) have confirmed that maternal behavior can be altered by exposure to BPA and other EDCs during gestation and lactation. It is well known that variation in maternal care can be responsible for differences in offspring in the rate of maturation, such as growth rate, and the subsequent neuroendocrine and behavioral responses associated with epigenetic changes [56].…”
Section: Mothersmentioning
confidence: 99%